2021
DOI: 10.1177/10732748211009952
|View full text |Cite
|
Sign up to set email alerts
|

Economic Burden of Colorectal Cancer: A Case of Fars, Iran

Abstract: Among cancers, colorectal cancer is the third most common cancer in the world and the fourth leading cause of cancer deaths worldwide. Some studies have shown that the incidence of colorectal cancer is increasing in Iran and in Fars province. The present study aimed to determine the economic burden of colorectal cancer in patients referred to the referral centers affiliated to Iran, Shiraz University of Medical Sciences in 2019 from the patients’ perspective. This is a partial economic evaluation and a cost-of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Luengo-Fernandez et al found that breast, colorectal and lung cancers had the highest costs among all types of cancers (Luengo-Fernandez et al, 2013). Broadly, the highest cost was prominent with surgical services for colorectal, stomach and lung cancers, which Jafari et al in their study showed that the surgical service has the highest cost for colorectal cancer treatment (Jaffari et al, 2021). Regarding stomach and lung cancers treatment cost there isn't any research to specify the highest costs of treatment services (Zhang et al, 2020;Kutikova et al, 2005;Joen et al, 2019).…”
Section: Discussionmentioning
confidence: 98%
“…Luengo-Fernandez et al found that breast, colorectal and lung cancers had the highest costs among all types of cancers (Luengo-Fernandez et al, 2013). Broadly, the highest cost was prominent with surgical services for colorectal, stomach and lung cancers, which Jafari et al in their study showed that the surgical service has the highest cost for colorectal cancer treatment (Jaffari et al, 2021). Regarding stomach and lung cancers treatment cost there isn't any research to specify the highest costs of treatment services (Zhang et al, 2020;Kutikova et al, 2005;Joen et al, 2019).…”
Section: Discussionmentioning
confidence: 98%
“…15 On the other hand, the results of various studies indicated very high costs of treating colorectal cancer in stage IV. [16][17][18] Chemotherapy drugs account for the largest share of the total costs paid by cancer patients. [19][20][21] The fact that many chemotherapy drugs are imported and the effect of inflation and currency price changes are among the reasons for the high cost of chemotherapy drugs.…”
Section: Introductionmentioning
confidence: 99%